Pneumocephalus following Dorsal Laminectomy: An Unusual Complication - Kumar, Brajesh (Asian J Neurosurg, 2017)
A 16-year-old male presented at Bangur Institute of Neurosciences Neurosurgery Outpatient Department with history of gradually progressive paraparesis for 5 months associated with stiffness, urinary hesitancy, and urge incontinence for last 2 months. Magnetic resonance imaging spine was done which showed cystic intradural extramedullary space occupying lesion at D4/D5 to D9. Patient had 2 episodes of generalized tonic–clonic seizure on the day 4. Computed tomography scan showed pneumocephalus. Histopathological examination report was that of nonspecific inflammatory cyst.